Photonics Breakthroughs 2024: Narrow-Linewidth Lasers in the Visible and Near-Infrared - Artem Prokoshin; Michael Gehl; Scott Madaras; Weng W. Chow; Yating Wan (IEEE Photonics Journal)
Narrow-linewidth lasers enable a variety of high-precision applications, such as sensing, optical clocks, and microwave frequency generation. Advances in photonic integration in the last decade led to the development of ultra-low-noise integrated semiconductor lasers, mostly in the telecom wavelength range. In recent years, the demand for high-performance lasers at shorter wavelengths skyrocketed, driven by applications in sensing and atom trapping. Low-noise lasers are of particular importance in this spectral range, as they are essential for optical clocks. Here, we will review recent progress in narrow-linewidth lasers at shorter wavelengths, present results on a hybrid-integrated low-noise laser at 780 nm and discuss the perspectives and challenges of high-performance semiconductor lasers in the visible and near-infrared.